2018
DOI: 10.1177/0264619618775765
|View full text |Cite
|
Sign up to set email alerts
|

The perception and use of technology within braille instruction: A preliminary study of braille teaching professionals

Abstract: A convenience sample (n = 35) of Teachers of Students with Visual Impairments (TVIs) and Rehabilitation Specialists completed a survey about their instructional techniques and perspectives on the relationship between braille and technology. While 62.5% of TVIs and Rehabilitation Specialists working with children, adolescents, or adults use technology in braille instruction, only 26.3% of those working with seniors use technology when teaching these clients. Rehabilitation Specialists felt significantly less kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Several participants in this study found it hard to teach braille and help support the use of braille technology devices such as braille notetakers in remote learning environments. Contrary to the claims of Martiniello et al (2018) that TVIs perceived the use of technology in braille instruction as a motivator and as a tool that can generate more positive learning outcomes, participants in this study reported frustrations of students around using devices for access and instructions of braille. This finding highlights the importance of professional development training on blindness technologies as it may be difficult to teach braille virtually without TVIs being proficient in such technologies themselves.…”
Section: Discussioncontrasting
confidence: 99%
“…Several participants in this study found it hard to teach braille and help support the use of braille technology devices such as braille notetakers in remote learning environments. Contrary to the claims of Martiniello et al (2018) that TVIs perceived the use of technology in braille instruction as a motivator and as a tool that can generate more positive learning outcomes, participants in this study reported frustrations of students around using devices for access and instructions of braille. This finding highlights the importance of professional development training on blindness technologies as it may be difficult to teach braille virtually without TVIs being proficient in such technologies themselves.…”
Section: Discussioncontrasting
confidence: 99%
“…A federal report published by the CNIB and other vision care associations highlighted the service gaps for certain populations in Canada, including the young, older adults, and Indigenous populations (National Coalition for Vision Health, 2010). It was found that technology, though having a promising role to benefit patients with VL, is often not available or used, for instance, Argus II retinal prosthesis in VR or use of technology for braille instruction to older clients (Markowitz et al, 2018; Martiniello et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We also examined item metadata and telemetry data coding and observational ratings due to the cautions in interpreting this type of data from BVI test takers (i.e., misinterpreting log files or other output, or variations in what can be captured due to 3 rd party assistive technology devices, Laitusis, 2022). This exploration provided insight to the importance of test administrator training so that the navigation assistance for the assistive technology is provided equitably across the different teachers of the blind and visually impaired and test administrators (e.g., Martiniello et al, 2018).…”
Section: Discussionmentioning
confidence: 99%